Preparation and characterization of a novel ethanol gas sensor based on FeYO3 microspheres by using orange peels as bio-templates. (July 2020) - Cao, P.F.; Ma, S.Y.; Xu, X.L.; Wang, B.J.; Almamoun, Omer; Han, T.; Xu, X.H.; Pei, S.T.; Zhang, R.; Zhang, J.L.; Liu, W.W.
Abstract: The perovskite Iron Yttrium Oxide (FeYO3 ) microspheres on the basis of bio-templates with orange peels have been successfully obtained by a facile hydrothermal 'green synthesis' along with multifarious characterization techniques. The XRD demonstrated that the synthesized sample was single phase FeYO3 with a hexagonal perovskite structure. Moreover, the solid microspheres with relatively rough surfaces were displayed by SEM and TEM. Benefiting from this fact, the sensor based on p-type semiconductor FeYO3 microspheres showed good gas sensing characteristics towards ethanol at the optimum operating temperature of 330 °C with a low detection limit (1 ppm), good repeatability and fast response/recover time, etc. Accordingly, this work supplies a good experimental basis for FeYO3 as a novel semiconductor gas sensing material soon. Highlights: The FeYO3 microspheres have been successfully obtained by a facile hydrothermal 'green synthesis'. A novel semiconductor gas sensing material FeYO3 was firstly prepared by using orange peels as bio-templates. The FeYO3 gas sensor showed good sensing properties towards ethanol.